The Effectiveness of Multimodel in Physics Learning to Train Students' Problem-Solving Skills - Ansari, Rahmat Al Farej; M, Abdul Salam; Dewantara, Dewi (Universitas Lambung Mangkurat, 2025)
The low ability of students to solve problems is caused by a lack of understanding of concepts and their inability to apply solutions to the problems given. In this regard, this study was conducted to overcome existing problems by applying multimodel learning. The subjects involved in this quantitative study had a pre-experimental design, namely 28 students of class XI A at one of the State Senior High Schools in Banjarmasin City. The data collection instrument was a learning outcome test that measured problem-solving abilities before and after the learning process. The study results showed increased learning outcomes, especially in students' problem-solving abilities, with an increased score of 52.4, which was classified as the medium category. Based on these results, the multimodel learning can successfully engage students in physics learning by enhancing their problem-solving skills.